Pelvic floor muscle strength evaluation in different body positions in nulliparous healthy women and its correlation with sexual activity - Monica Orsi Gameiro; Luciana Miraglia; Luiz Felipe Orsi Gameiro; Carlos Roberto Padovani; Joao Luiz Amaro (International Brazilian Journal of Urology, 2013)
Objective The aim of this study was to assess pelvic floor muscle (PFM) strength in different body positions in nulliparous healthy women and its correlation with sexual activity. Materials and Methods Fifty healthy nulliparous women with mean age of 23 years were prospectively studied. Subjective evaluation of PFM was assessed by transvaginal digital palpation (TDP) of anterior and posterior areas regarding the vaginal introitus. A perineometer with inflatable vaginal probe was used to assess the PFM strength in four different positions: supine with extended lower limbs (P1); bent-knee supine (P2); sitting (P3); standing (P4). Results Physical activity, 3 times per week, was reported by 58% of volunteers. Sexual activity was observed in 80% of women and 82% of them presented orgasm. The average body mass index (BMI) was 21.76 kg/m2, considered as normal according World Health Organization (WHO). We observed that 68% of volunteers were conscious about the PFM contraction. TDP showed concordance of 76% when anterior and posterior areas were compared (p = 0.00014). There was not correlation between PFM strength and orgasm in subjective evaluation. The PFM strength was significantly higher in standing position when compared with the other positions (p < 0.000). No statistical difference was observed between orgasm and PFM strength when objective evaluations were performed. Conclusions There was concordance between anterior and posterior areas in 76% of cases when subjective PFM strength was assessed. In objective evaluation, higher PFM strength was observed when volunteers were standing. No statistical correlation was observed between PFM strength and orgasm in nulliparous healthy women.